2016
DOI: 10.1137/15m1051373
|View full text |Cite
|
Sign up to set email alerts
|

An Advective-Spectral-Mixed Method for Time-Dependent Many-Body Wigner Simulations

Abstract: As a phase space language for quantum mechanics, the Wigner function approach bears a close analogy to classical mechanics and has been drawing growing attention, especially in simulating quantum many-body systems. However, deterministic numerical solutions have been almost exclusively confined to one-dimensional one-body systems and few results are reported even for one-dimensional two-body problems. This paper serves as the first attempt to solve the time-dependent many-body Wigner equation through a grid-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 38 publications
0
36
0
Order By: Relevance
“…Here we assume that V w decays and thus ignore the periodic images. A necessary and sufficient condition for the truncated Wigner equation (3.1) to conserve the mass has been given in [13] and reads L k ∆y = 2π, (3.4) where L k = k max − k min represents the length of k-domain. In x-space, the popular quantum transitive boundary condition will be adopted hereafter as did in [12].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we assume that V w decays and thus ignore the periodic images. A necessary and sufficient condition for the truncated Wigner equation (3.1) to conserve the mass has been given in [13] and reads L k ∆y = 2π, (3.4) where L k = k max − k min represents the length of k-domain. In x-space, the popular quantum transitive boundary condition will be adopted hereafter as did in [12].…”
Section: Methodsmentioning
confidence: 99%
“…where n(x, t) is the particle density and j(x, t) the current density [13]. The other is the energy conservation…”
Section: Quantum Mechanics In Phase Spacementioning
confidence: 99%
“…Pseudo-spectral methods have been successfully used to accurately treat the Wigner function in Refs. [16,17]. However, in this section, we do not present such a highly optimized implementation.…”
Section: B Phase Space Discretizationmentioning
confidence: 99%
“…While having been studied for a long time [14], direct discretization using well-designed finite difference approaches has recently been improved by using the weighted essentially non-oscillating scheme (WENO) to prevent erroneous oscillations [15]. In other work, it has also been shown that the Wigner function can be solved in a robust way using adaptive pseudo-spectral methods in the form of massconserving spectral element methods [16,17]. In these methods, the carefully crafted spectral decomposition of the Wigner function enables the oscillatory components introduced by the Wigner kernel to be solved exactly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation